Pengaruh Leader-Member Exchange dan Work-Life Balance terhadap Kinerja Pegawai melalui Kepuasan Kerja pada PT Bank Nagari Cabang Pasar Raya - Siti Medira Khairunnisa; Robby Dharma; Bayu Pratama Azka (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the influence of Leader Member Exchange (LMX) and Work Life Balance (WLB) on employee performance with job satisfaction as an intervening variable at PT. Bank Nagari Pasar Raya Branch. LMX represents the quality of reciprocal relationships between leaders and subordinates, including trust, support, and effective communication, while WLB reflects the balance between work demands and employees' personal lives. Employee performance is measured based on aspects of quantity, quality, efficiency, discipline, and initiative in completing work. Job satisfaction is positioned as a mediating variable believed to strengthen the influence of LMX and WLB on employee performance. This study uses a descriptive quantitative method with a survey approach. Primary data were obtained by distributing questionnaires to all 92 active employees, so the sampling technique used was saturated sampling. Data analysis was carried out using Structural Equation Modeling (SEM) using SmartPLS 3 software to test direct and indirect relationships between variables. The results showed that LMX has a positive and significant effect on job satisfaction, where a harmonious relationship between leaders and subordinates can increase employee satisfaction with their work. WLB was also shown to have a positive and significant effect on job satisfaction, indicating that a good work-life balance can increase employee motivation and well-being. Furthermore, LMX and WLB directly influence performance, and job satisfaction is shown to mediate the relationship, thus strengthening the influence of both on employee performance. These findings provide practical implications for the management of PT. Bank Nagari, namely the importance of strengthening the quality of interactions between superiors and subordinates, providing emotional support, and implementing flexible work policies that support employee welfare.